cGAS-STING pathway in pathogenesis and treatment of osteoarthritis and rheumatoid arthritis - Yang, XiCheng; Zhao, LiLi; Pang, YinQuan (Frontiers in Immunology, 2024)
Osteoarthritis (OA) and Rheumatoid Arthritis (RA) are significant health concerns with notable prevalence and economic impact. RA, affecting 0.5% to 1.0% of the global population, leads to chronic joint damage and comorbidities. OA, primarily afflicting the elderly, results in joint degradation and severe pain. Both conditions incur substantial healthcare expenses and productivity losses. The cGAS-STING pathway, consisting of cyclic GMP–AMP synthase (cGAS) and stimulator of interferon genes (STING), is a crucial component of mammalian immunity. This pathway is responsible for detecting foreign DNA, particularly double-stranded DNA (dsDNA), triggering innate immune defense responses. When cGAS recognizes dsDNA, it catalyzes the synthesis of cyclic GMP–AMP (cGAMP), which then binds to and activates STING. Activated STING, in turn, initiates downstream signaling events leading to the production of interferons and other immune mediators. The cGAS-STING pathway is essential for defending against viral infections and maintaining cellular balance. Dysregulation of this pathway has been implicated in various inflammatory diseases, including arthritis, making it a target for potential therapeutic interventions. Understanding the intricate molecular signaling network of cGAS-STING in these arthritis forms offers potential avenues for targeted therapies. Addressing these challenges through improved early detection, comprehensive management, and interventions targeting the cGAS-STING pathway is crucial for alleviating the impact of OA and RA on individuals and healthcare systems. This review offers an up-to-date comprehension of the cGAS-STING pathway’s role in the development and therapeutic approaches for these arthritis types.